Calibrating the magnitude of the Toarcian carbon cycle perturbation. (13th May 2015) - Suan, Guillaume; van de Schootbrugge, Bas; Adatte, Thierry; Fiebig, Jens; Oschmann, Wolfgang
Abstract Sedimentary rocks recording the Toarcian oceanic anoxic event (T‐OAE) are marked by a negative carbon isotope excursion (CIE) reaching up to −7‰ and ranking among the largest known in the Phanerozoic. These records suggest a dramatic perturbation of the carbon cycle that has been linked to the transfer of juvenile carbon from the endogenic to the exogenic reservoirs. Nevertheless, the magnitude of the Toarcian CIE varies significantly from one substrate to another, hence complicating mass balance evaluation of the potential driving mechanisms. Here we show, using high‐resolution, paired records of δ13Ctotal organic carbon (TOC) and hydrogen index from the Denkingen core and Dotternhausen quarry (Germany), that the amplitude of the negative CIE in marine organic matter is considerably exaggerated by changes in organic matter sourcing. Our corrected 3–4‰ CIE implies a constant carbon isotope fractionation between organic and carbonate carbon across the T‐OAE and may point to a prominent role of cyanobacteria as organic matter producers during the Early Jurassic. These results also suggest that the difference between inorganic and organic carbon isotope values in marine strata constitutes a poor proxy of pCO2 levels across the T‐OAE. Moreover, this corrected 3–4‰ CIE, together with evidence for >5°C seawater warming across the T‐OAE, point to the input of >25, 000 Gt C with much more 13C‐enriched signature than previously modeled. Our results thus allow reconciling inorganic and organic δ13C records of the T‐OAE and have important implications for the evaluation of their causal mechanisms.